YOUTH RADICALISM: FACTORS, INSTITUTIONAL FORMS, FEATURES - Elena Vladimirovna Efanova (Современная наука и инновации, 2022)
Scientific approaches to radicalism studying are presented in article, features and factors of his emergence among young people are defined. The author has specified the reasons of radicalization of youth, and her functional potential